2008
DOI: 10.1606/1044-3894.3759
|View full text |Cite
|
Sign up to set email alerts
|

Matched Comparison of Children in Kinship Care and Foster Care on Child Welfare Outcomes

Abstract: The documented growth of kinship care has boldly thrust this topic into the forefront of child welfare practice. This study compares the permanency, safety, and stability outcomes for a matched group of children placed in kinship care and foster care. After controlling for demographic and placement characteristics, children in kinship care had significantly fewer placements than did children in foster care, and they were less likely to still be in care, have a new allegation of institutional abuse or neglect, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 12 publications
2
46
0
Order By: Relevance
“…This study also found that 92 per cent of females and 86 per cent of males in detention had a diagnosed psychological disorder, including an attention or behavioural disorder, a substance abuse disorder, an anxiety or other mood disorder, or a psychotic disorder. Other studies reinforce these findings (Lawrence, Carlson, & Egeland, 2006;Kessler et al, 2008;Tarren-Sweeney, 2008;Winokur, Crawford, Longobardi, & Valentine, 2008).…”
Section: Youth Mental Healthsupporting
confidence: 53%
“…This study also found that 92 per cent of females and 86 per cent of males in detention had a diagnosed psychological disorder, including an attention or behavioural disorder, a substance abuse disorder, an anxiety or other mood disorder, or a psychotic disorder. Other studies reinforce these findings (Lawrence, Carlson, & Egeland, 2006;Kessler et al, 2008;Tarren-Sweeney, 2008;Winokur, Crawford, Longobardi, & Valentine, 2008).…”
Section: Youth Mental Healthsupporting
confidence: 53%
“…Furthermore, although some research has indicated that kinship care does not impede adoption rates (Connell et al, 2006;Koh & Testa, 2008;Winokur et al, 2008), it makes sense that adoption would be less likely for children in kinship care if relatives are more comfortable with guardianship arrangements than adoptions (Testa, 2002). In sum, the findings on initial placement type indicated that connections to family or kin were important for reunification and even more so for guardianship.…”
Section: Important Predictors Across Permanency Outcomesmentioning
confidence: 90%
“…Placement type was frequently defined as the type of initial placement, to include non-kin foster care, kinship foster care, group homes, and, sometimes, emergency shelters. In general, placement type was almost always found to have a significant association with foster care exits, (Connell, et al, 2006;Courtney & Wong, 1996;Goerge, 1990;Harris & Courtney, 2003;Park & Ryan, 2009;Smith, 2003;Vogel, 1999;Wells & Guo, 1999;Winokur, Crawford, Longobard, & Valentine, 2008) though the specifics vary by type of exit and type of placement, and a few studies found contradictions (Courtney, et al, 1997;Koh & Testa, 2008;PabustanClaar, 2007;Potter & Klein-Rothschild, 2002). Specifically, initial placement in group home settings or emergency shelters lowered the likelihood of reunification (Connell, et al;Courtney & Wong;Park & Ryan, 2009) and adoption (Connell, et al).…”
Section: Type Of Placementmentioning
confidence: 99%
See 2 more Smart Citations